Better together: novel methods for measuring and modeling development of executive function diversity while accounting for unity - Younger, Jessica Wise; O’Laughlin, Kristine D.; Anguera, Joaquin A.; Bunge, Silvia A.; Ferrer, Emilio E.; Hoeft, Fumiko; McCandliss, Bruce D.; Mishra, Jyoti; Rosenberg-Lee, Miriam; Gazzaley, Adam; Uncapher, Melina R. (Frontiers in Human Neuroscience, 2023)
Executive functions (EFs) are linked to positive outcomes across the lifespan. Yet, methodological challenges have prevented precise understanding of the developmental trajectory of their organization. We introduce novel methods to address challenges for both measuring and modeling EFs using an accelerated longitudinal design with a large, diverse sample of students in middle childhood (N = 1,286; ages 8 to 14). We used eight adaptive assessments hypothesized to measure This is a provisional file, not the final typeset article 2 three EFs, working memory, context monitoring, and interference resolution. We deployed adaptive assessments to equate EF challenge across ages and a data-driven, network analytic approach to reveal the evolving diversity of EFs while simultaneously accounting for their unity. Using this methodological paradigm shift brought new precision and clarity to the development of these EFs, showing these eight tasks are organized into three stable components by age 10, but refinement of composition of these components continues through at least age 14.